Persepsi Generasi Muda terhadap Minat Bertani di Kawasan Pariwisata Tanah Lot (Kasus Subak Gadon III, Tabanan) - NI MADE LOSVITASARI; I KETUT SURYA DIARTA; I GUSTI AYU OKA SURYAWARDANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Perception of Young Generations’ Interest in Farming in Tanah LotTourism Area (The Case of Subak Gadon III, Tabanan) The rapid development of tourism will affect subak : that is, the transformation oflabor, the occurrence of land conversion, and the occurrence of water usecompetition. Tourism will have an impact on farming interest, especially the youngergeneration of farm households in Subak Gadon III, knowing that this subak is locatedin the tourism area. The purpose of this study was to analyze perceptions anddifferences in the perception of younger generation of non-tourism and youngergeneration of tourism about the impact of tourism on farming interest of the youngergeneration of farm households in Subak Gadon III, Tabanan. Data analysis methodused was descriptive-qualitative and quantitative.The results showed that the perception of the younger generation of non-tourismabout the impact of tourism on the farming interest of the younger generation wasclassified with a score of 3,32. The younger generation of non-tourism had aperception that the existence of tourism sufficiently influenced the farming interest ofthe young generation, but it did not make the non-tourism youth switch to tourism.The younger generation of tourism showed that tourism had a high impact on theinterest of farming the younger generation with a score of 3,55. The younggeneration of tourism has a perception that tourism was the most appropriate choicebecause for them the tourism sector is very supportive of its life. There is adifference in the impact of tourism on farming interest in the younger generation ofnon-tourism and young generation of farm households' tourism in Subak Gadon III,Beraban, Tabanan. This difference was seen in 3 parameters of a total of 14parameters.Suggestions that can be made for this research are for Subak Gadon III in the futureto be able to initiate a new breakthrough by involving the young generation invarious activities in subak life to attract farmers especially the younger generation offarm households in Subak Gadon III, Tabanan.